2011
DOI: 10.1002/oa.1300
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Columbian Tuberculosis in Northwest Argentina: Skeletal Evidence from Rincón Chico 21 Cemetery

Abstract: Systematic excavation of collective burial sites makes possible the recovery of skeletal series which may show bony evidence of infectious pathological conditions. This paper presents the first evidence of the existence of tuberculosis in prehistoric populations of NW Argentina with a subsistence economy based on agriculture and pastoralism. The study was carried out on individuals from Rincón Chico 21 cemetery, a burial site located in the Santa María Valley, Catamarca, used between the Late Ceramic Period an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…So far, the earliest primary evidence of TB comes from mummified individuals found in the Atacama Desert (acid-fast bacilli identified in the lungs and in the healed Ghon's complex) dating from the first millennium CE (Allison et al, 1981in Mackowiak et al, 2005. Other skeletal evidence of TB has been found (see Roberts and Buikstra, 2003;Mackowiak et al, 2005;Arrieta et al, 2014), in some cases confirmed with DNA and mycolates analyses (e.g. Luna et al, 2018).…”
Section: Short History Of Tuberculosismentioning
confidence: 96%
“…So far, the earliest primary evidence of TB comes from mummified individuals found in the Atacama Desert (acid-fast bacilli identified in the lungs and in the healed Ghon's complex) dating from the first millennium CE (Allison et al, 1981in Mackowiak et al, 2005. Other skeletal evidence of TB has been found (see Roberts and Buikstra, 2003;Mackowiak et al, 2005;Arrieta et al, 2014), in some cases confirmed with DNA and mycolates analyses (e.g. Luna et al, 2018).…”
Section: Short History Of Tuberculosismentioning
confidence: 96%
“…; Arrieta et al. ). In clinical settings, periosteal rib lesions are an occasional finding, often reported in patients with chronic conditions of the pleura and lungs, such as tuberculosis (Eyler et al.…”
Section: Introductionmentioning
confidence: 97%
“…Pfeiffer, 1984Pfeiffer, , 1991Molto, 1990;Wakely et al 1991;Lambert, 2002;Walker & Henderson, 2010;Wescott et al 2010) or associated with other bony changes, such as massive vertebral destruction (e.g. Haas et al 2000;Suzuki & Inoue, 2007;Suzuki et al 2008;Arrieta et al 2011). In clinical settings, periosteal rib lesions are an occasional finding, often reported in patients with chronic conditions of the pleura and lungs, such as tuberculosis (Eyler et al 1996;Guttentag & Salwen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…All these investigations contribute to the great challenge of increasing our knowledge of the health of human popula tions that inhabited southern South America in the past: for instance, enamel hypoplasia, porotic hyperostosis, cribra orbitalia and Harris lines (L'Heureux, 2000; Novellino and Gil, 2007;Gómez Otero and Novellino, 2011;Fabra and González, 2012), degenerative joint diseases and entheseal changes Scabuzzo, 2012), evalu ations of oral health, dental size, and hypocalcification (L'Heureux, 2000; Bernal et al, 2007;Luna, 2010;Luna and Aranda, 2010;Menéndez, 2010;Flensborg, 2011;see Bernal and Luna, 2011), analyses of bone mineral density ), paleoparasitological studies Fugassa et al, 2010), research on infectious García Laborde et al, 2010;Flensborg et al, 2013;Arrieta et al, 2014), traumatic (Gordón and Bosio, 2012;Gordón, 2013) and neoplastic diseases (Luna et al, 2008). Some paleoepidemiological and paleodemographical stud ies were also carried out (García Guraieb, 2006;Luna, 2006Luna, , 2012Berón et al, 2012;Flensborg et al, 2013).…”
mentioning
confidence: 99%